The EdTech Hub’s approach to amplifying impact through engagement – The EdTech Hub - Jamieson Eberhardt, Molly (EdTech Hub, 2019)
If you have spent time working in the education sector, you’ll know that even marginal gains are worthy of celebration. Those of us involved in launching the EdTech Hub know this well — from our experience as teachers, researchers, advisers, programme implementers, and civil servants. Nevertheless, we have the ambition to help accelerate progress toward quality education at an unprecedented rate. We of course know that sustainable change often takes time, and we respect hard-earned marginal gains. But what we’re really after is improvement in education outcomes at a pace that matches the urgency of the problem — think millions of children receiving quality education within a decade, not in decades.
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Five starting points on innovation for the EdTech Hub – The EdTech Hub - Simpson, Lea (EdTech Hub, 2019)
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech Hub Research and Innovation to fulfill the potential of EdTech - Nicolai, Susan (EdTech Hub, 2019)
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Introducing the EdTech Hub’s programme for research in low-income countries – The EdTech Hub - Hennessy, Sara (EdTech Hub, 2019)
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Methodology for literature reviews undertaken by the EdTech Hub - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Sara Hennessy; David Hollow; Katy Jordan; Kevin Martin; Mary Murphy; Hannah Walker (EdTech Hub, 2019)
An output of the EdTEch Hub
Keywords: LP: English; R:Literature review, systematic review; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _dont_post_PDF; _yl:h; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Hello, I’m Björn, Director of Research – The EdTech Hub - Haßler, Björn (EdTech Hub, 2019)
I’m Dr Björn Haßler, one of the three Directors of Research for the programme. Research, and particularly at-scale research, is a core focus for the #EdTechHub and that’s why we have three Directors of Research, who will also introduce themselves. I am — we all are — extremely happy that we have been awarded the programme. We, like all our competitors, worked hard for around 1.5 years until the final submission. However, this work paid off! It means we can get going on the important mission.
Keywords: _DOILIVE; _EdTechHub_Output; _yl:r; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Complexity and Considerations in Delivering Adaptive Learning Digital Services - Proctor, Jamie (EdTech Hub, 2019)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Literature Reviews of Educational Technology Research in Low- and Middle-Income Countries: An audit of the field - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
Keywords: LP: English; R:Literature review, systematic review; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:g; _zenodoETH:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode; educational technology, EdTech, low-income countries, literature review

Reviewing the research literature in educational technology for development: Balancing rigour and inclusivity - Jordan, Katy (EdTech Hub, 2019)
Keywords: LP: English; R:Literature review, systematic review; _DOILIVE; _EdTechHub_Output; _zenodoETH

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Systemic Mixed-Methods Research — A conceptual framework for EdTech research along the IDIA scale - Haßler, Björn; Hennessy, Sara; Hollow, David; Simpson, Lea; Carter, Alice; Damani, Kalifa; Francis, Gill; Jordan, Katy; McIntyre, Nora; Mitchell, Joel (EdTech Hub, 2019)
Keywords: LP: English; R:Mixed methods; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF; _yl:f; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Research publication strategy and proposed publications - Haßler, Björn; McIntyre, Nora; Hollow, David; Jordan, Katy; Hennessy, Sara; Brugha, Meaghan; Mitchell, Joel (EdTech Hub, 2019)
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Country list with HDI, iHDI, MPI and Gini (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
This is pdf of a country list with HDI, iHDI, MPI and Gini. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB (which will also be available as a data file).
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:q; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Refugee education: The crossroads of globalization - Dryden-Peterson, Sarah (Educational Researcher, 2016)
In this article, I probe a question at the core of comparative education—how to realize the right to education for all and ensure opportunities to use that educ...
Keywords: AA - to delete; Edtech hub/ refugees education

Making innovation work for girls and women in Tanzania, Tanzania: HDIF, 2017 - Bangser, Maggie; Davies, Emma; Lähde, Kristiina; McGinty, David (HDIF Tanzania, 2017)

Teacher educators and OER in East Africa: Interrogating pedagogic change - Wolfenden, Freda; Auckloo, Pritee; Buckler, Alison; Cullen, Jane (Adoption and Impact of OER in the Global South, 2017)
This study examines the use of Open Educational Resources (OER) in six teacher education institutions in three contrasting East African settings – Mauritius, Tanzania and Uganda – all of which had previous engagement with OER initiatives. Drawing primarily on interviews with teacher educators, the study examines how and when teacher educators engage with OER, the factors that support and constrain sustained OER engagement, and the influence of such engagement on their teaching practice. It seeks to answer the following three research questions: What kinds of OER are teacher educators aware of and how do they access them? How and for what purpose are they using the OER? What intended and enacted pedagogic practices are associated with OER use? The study takes a sociocultural approach, paying attention to the practices of teacher educators and the context and culture of the teacher education institutions within which they work, as well as the national policies relevant to these institutions. Surveys were sent to academic staff at each of the participating institutions who were, or had been, involved in curriculum development work involving OER. Male and female educators from different disciplinary backgrounds and with varying roles and periods of service within the institutions were targeted. From the respondents, selected individuals were asked to participate in semi-structured interviews concerning OER and their pedagogical practices. A total of 58 surveys were completed by teacher educators along with 36 in-depth teacher educator interviews and six institutional stakeholder interviews. The results of the study indicate that teacher educators’ understanding and use of OER is highly fragmented, with little traction at department or institutional level. At all the study sites there was dissonance between the ways in which individual educators are using OER and the dominant institutional values and discourse. There were also numerous structural and cultural factors acting to limit agency with regards to OER use. The demands of curriculum and assessment, professional identity, digital skills, provision of equipment and connectivity, values and weak cultures of collaboration all exerted an influence and enabled or constrained teacher educators’ efforts to achieve agency with OER. For a small number of teacher educators (OER “champions”), OER provides a tool for extending their agency to move towards more participatory practices. In their interviews, several of these educators spoke of the formative role of academic training and many were linked to external OER networks. These elements of historic identity formation influence how they respond to OER, and enhance their confidence to take risks in moving beyond conventional practice. Enabling educators to act in an agentive way with OER is not easy. Moving forward, attention should be given to issues of access so that educators are able to locate and view OER relatively easily and experiment with their use. This study recommends that time be made available for educators to enhance their skills in working digitally and to become familiar with principles of learning design such that these become integral dimensions of their professional identity. It is also argued that extending and deepening engagement with OER requires opportunities for professional dialogue and collaboration to support the development of productive educator identities with OER and transformation of the community’s field of practice.
Keywords: East Africa; Global South; Mauritius; OEP; OER; Open Education; Open Educational Resources; ROER4D; Tanzania; Uganda; _not_EdTechHub; _zenodoOTHER; agency; pedagogy; teacher education

Tanzania 2017 field testing report: Can out-of-school children make learning gains with Kitkit School? - Kitkit School (Kitkit School, 2017)

Transforming education for girls in Tanzania and Nigeria: Cross country analysis of endline research studies - Unterhalter, Elaine; Heslop, Jo (ActionAid, 2012)
This cross country summary of the findings from the endline study conducted for the TEGINT project highlights a number of issues of particular pertinence to the community of policy makers, practitioners, and researchers concerned with gender equality, rights and girls’ education. Firstly, the considerable expansion of education provision at primary and junior secondary levels enhances girls’ enrolment, attendance, progression, attainment and empowerment. However, there are regional and locational differences, and the effects of the emergence of private schools on gender equality and girls’ empowerment merits careful scrutiny. It is a matter of concern, that despite the introduction of free primary education, schools continue to charge levies and that the costs of improving education are being passed down to the poorest. Secondly, there are clear indications that girls’ clubs give an important space for girls to learn about their rights and confidence to articulate solutions to their problems. This is the case both when girls in clubs come from higher performing girls in terms of class position and more marginalised girls. Thus girls clubs, widely used in many projects throughout Africa, but not till now well evaluated, appear an important strategy to continue to support. Thirdly, rurality appears as a particular condition of marginalisation, associated with higher levels of gender inequality. This is evident from the lower levels of girls’ empowerment in rural schools, and differences in articulating solutions. Thus particularly engaged interventions are needed with girls in remote areas to support empowerment. Fourthly, while improving teacher qualifications and engagement with gender equality is a necessary condition for enhancing education rights for all children, this is not a standalone intervention, and needs to be supported by other initiatives, possibly associated with teachers’ pay, work conditions and status. Fifthly, an intervention like TEGINT, appears particularly useful in helping to break the silence around gender based violence, however, such an intervention cannot be seen in isolation from work on other aspects of gender inequalities, poverty, and limited social provision. In a country like Tanzania, where there is more legislation and political action around gender equality than in Nigeria, girls, even the poorest, appear more knowledgeable about rights. Gender equality and girls’ education cannot thus be separated from other initiatives on rights, social development and addressing injustice.